Reject Dokumen Impor dan Efisiensi Biaya pada Proses Customs Clearance di Perusahaan Freight Forwarding - Setianti, Elisa; Purbasari, Ratih; Novel, Nurlillah (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2025)
AbstractThis study aims to identify the factors causing errors in import documents that lead to the issuance of Document Rejection Notices (NPP) and to analyze their impact on operational cost efficiency in the customs clearance process at PT X. The research employs a descriptive qualitative approach with data collection techniques including interviews, observation, and literature review. Informants were selected purposively and consisted of operational staff and managers directly involved in the import process. The findings reveal that the most common errors involve discrepancies in the Harmonized System (HS) Code, followed by inconsistencies between the Import Declaration (PIB) and Bill of Lading (B/L), incomplete documents, and differences between original and copy B/Ls. As a result, the company experienced delays in the release of goods and a significant increase in operational costs amounting to IDR 282,019,609 during the period of January to June 2024. These costs include administrative penalties, import duty adjustments, and storage and handling fees. This study contributes by offering strategic recommendations for the company, including improvements in document verification procedures, development of standardized operating procedures (SOPs), and enhanced employee understanding of goods classification and customs regulations to improve efficiency and competitiveness in international logistics services.